Modelling the Impact of Occupational Health and Safety, Work Motivation, and Work Discipline on Employee Performance and Achievement Using Structural Equation Modelling - Syaifudin, Arif; Firdaus, Vera; Setiyono, Wisnu Panggah (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study examines the influence of occupational safety and health, work motivation, and work discipline on employee achievement and performance at PT. Lautan Kayu Abadi Sejahtera. The study employs a quantitative descriptive approach with a cluster sampling technique. The research was conducted at PT. Lautan Kayu Abadi Sejahtera, located on Jl. Raya Sumobito KM. 02, Betek Barat Village, Mojoagung District, Jombang Regency, East Java Province. The respondents consisted of 89 employees from the production department. Data were collected through observation and questionnaire distribution and subsequently analyzed using a quantitative approach. Furthermore, this study employs Structural Equation Modeling (SEM) with AMOS software. The SEM analysis was conducted in two stages: (1) measurement model analysis, which includes goodness-of-fit (GOFI), validity, and reliability tests to ensure model adequacy; and (2) structural model analysis, which comprises overall model feasibility testing, causal relationship analysis, and hypothesis testing.